グリーンランド氷床北西部SIGMA-Dアイスコア中の鉱物組成変動 - 永塚, 尚子 (2016)
極地に分布する氷河や氷床の上には，周囲の土壌や遠方の砂漠などを起源とする風送ダストが堆積し，毎年，涵養域の雪の層の中に保存される．これらのダストの量や経路，種類は供給源となる砂漠や氷床周辺の環境の変化に伴い，年とともに変動していると考えられる．したがって，氷床上に保存されているダストをアイスコアとして取り出して分析すれば，過去に氷床上に堆積したダストの変動を明らかにすることができ，さらには氷床上へのダストの輸送経路や供給源となる場所の変動を明らかにできる可能性がある．しかしながら，このようなダストの成分の分析やその供給源を特定する研究はまだ限られている．本研究では，微量でも分析が可能な走査型電子顕微鏡（SEM）を用いて，アイスコア試料中の鉱物の形態観察，および化学成分分析を行うことで，過去に氷床上に堆積したダストの起源および輸送経路の解明にアプローチすることを試みている．今回の発表では，2014年にグリーンランド氷床北西部で掘削されたアイスコア中の鉱物ダストのSEM観察結果，および組成変動について紹介する．さらに，2016年夏に行われた東グリーンランド氷床アイスコア掘削プロジェクト（EGRIP）での活動の様子についても紹介する． Snow and ice on glaciers and the ice sheet in the Arctic contain windblown mineral dusts derived from local sediments as well as distant deserts. Dust deposited on the ice sheet in the past can be obtained by ice core drilling, and the variations in their sources and transportation process can be reconstructed by particle analysis of ice cores. In this study, we analyzed morphology and surface chemistry of mineral dust particles in an ice core drilled at Northwest Greenland in 2014 with Scanning Electron Microscope (SEM, QUANTA FEG 450) and Energy Dispersive X-ray Spectrometer (EDS). Here we report the variations in size distributions and compositions of the ice core dust. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：12月14日（水）10:00-10:50 場所：C301（3階セミナー室） conference object